Meta-Analisis Pengaruh Bahan Ajar Terintegrasi Pendidikan Lingkungan Terhadap Hasil Belajar Siswa - Oktrisma, Yesni oktrisma (Universitas Negeri Padang, 2020)
This research was conducted to analyze some of the results of research that discusses physics teaching materials. Aims to describe the effect of environmental literacy teaching materials on learning outcomes The research method is quantitative descriptive. This research is a meta-analysis with a sample of 10 articles. Education is the most strategic way to instill, apply the values of sustainable development. The construction of this case is the development of students' thinking patterns as educational subjects that are prepared for the life to come. students must think logically and critically of solutions that will be offered indirectly to student learning outcomes. The study used a logical one-group pretest-posttest design on physics learning outcomes through the results of the journal effect size. The average of these journals is 0.64. medium category.